Analisis Faktor Penyebab Kesulitan Belajar Matematika Siswa Sekolah Dasar - Mahardiyanti, Taurinda (Cipta Media Harmoni, 2024)
Students continue to face learning difficulties during the process of learning mathematics. Disturbances in one or more basic psychological functions, such as understanding and using spoken or written language, are known as learning disabilities. The purpose of this study was to identify the elements that contribute to children's challenges in learning mathematics and to outline strategies to overcome these problems for students in grade II of Elementary School. Data for this qualitative descriptive study were collected through documentation, unstructured interviews, and observations. Triangulation and increased persistence were the data validity strategies used. On the other hand, data analysis involved collecting, reducing, presenting, and drawing conclusions from data. Students' poor attitudes towards learning mathematics, lack of interest in learning, low motivation to learn, and less than ideal physical health are internal influencing factors that come from within the students. External influences include the use of less than ideal learning materials, less diverse teaching strategies, classrooms that are still full of trash, lack of infrastructure and equipment, especially teaching aids, and the home environment. Low motivation and interest of students, as well as family and environmental conditions, are the root causes of learning challenges. Organizing additional and remedial lesson programs, motivating children verbally, and giving them rewards are the best efforts that can be made.